Comparison of brain MRI findings with language and motor function in the dystroglycanopathies. (14th February 2017) - Brun, Brianna N.; Mockler, Shelley R.H.; Laubscher, Katie M.; Stephan, Carrie M.; Wallace, Anne M.; Collison, Julia A.; Zimmerman, M. Bridget; Dobyns, William B.; Mathews, Katherine D.
Abstract : Objective: To describe the spectrum of brain MRI findings in a cohort of individuals with dystroglycanopathies (DGs) and relate MRI results to function. Methods: All available brain MRIs done for clinical indications on individuals enrolled in a DG natural history study (NCT00313677) were reviewed. Reports were reviewed when MRI was not available. MRIs were categorized as follows: (1) cortical, brainstem, and cerebellar malformations; (2) cortical and cerebellar malformations; or (3) normal. Language development was assigned to 1 of 3 categories by a speech pathologist. Maximal motor function and presence of epilepsy were determined by history or examination. Results: Twenty-five MRIs and 9 reports were reviewed. The most common MRI abnormalities were cobblestone cortex or dysgyria with an anterior-posterior gradient and cerebellar hypoplasia. Seven individuals had MRIs in group 1, 8 in group 2, and 19 in group 3. Language was impaired in 100% of those in MRI groups 1 and 2, and degree of language impairment correlated with severity of imaging. Eighty-five percent of the whole group achieved independent walking, but only 33% did in group 1. Epilepsy was present in 8% of the cohort and rose to 37% of those with an abnormal MRI. Conclusions: Developmental abnormalities of the brain such as cobblestone lissencephaly, cerebellar cysts, pontine hypoplasia, and brainstem bowing are hallmarks of DG and should prompt consideration of these diagnoses. Brain imaging in individuals with DG helps to predict outcomes, especially language development, aiding clinicians in prognostic counseling.